Bank networks: Contagion, systemic risk and prudential policy - I\~naki Aldasoro; Domenico Delli Gatti; Ester Faia (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
We present a network model of the interbank market in which optimizing risk averse banks lend to each other and invest in non-liquid assets. Market clearing takes place through a tâtonnement process which yields the equilibrium price, while traded quantities are determined by means of a matching algorithm. Contagion occurs through liquidity hoarding, interbank interlinkages and fire sale externalities. The resulting network configuration exhibits a coreperiphery structure, dis-assortative behavior and low density. Within this framework we analyze the effects of prudential policies on the stability/efficiency trade-off. Liquidity requirements unequivocally decrease systemic risk but at the cost of lower efficiency (measured by aggregate investment in non-liquid assets). Equity requirements tend to reduce risk (hence increase stability) without reducing significantly overall investment.
Keywords: D85; G21; G28; C63; L14; 330; banking networks; systemic risk; contagion; fire sales; prudential regulation